Reduced vascular NO bioavailability in diabetes increases platelet activation in vivo. - Schäfer, A; Alp, N; Cai, S; Lygate, C; Neubauer, S; Eigenthaler, M; Bauersachs, J; Channon, K (2004)
OBJECTIVE: Platelet activation is a feature of cardiovascular disease that is also characterized by endothelial dysfunction. The direct relationship between impaired endothelium-derived NO bioavailability and platelet activation remains unclear. We investigated whether acute inhibition of NO production modulates platelet activation in mice and whether specific rescue of endothelial function in diabetes modifies platelet activation. METHODS AND RESULTS: Intravenous injection of the NO synthase inhibitor N(G)-nitro-L-arginine methyl ester in wild-type (WT) mice significantly reduced platelet vasodilator-stimulated phosphoprotein (VASP) phosphorylation and increased platelet surface expression of P-selectin, CD40 ligand, and fibrinogen platelet binding, demonstrating that NO production exerts tonic inhibition of platelet activation in mice. Diabetes was induced by streptozotocin injection in WT or endothelial-targeted guanosine 5'-triphosphate cyclohydrolase I (GCH)-transgenic (GCH-Tg) mice protected from endothelial dysfunction in diabetes by sustained levels of tetrahydrobiopterin in vascular endothelium. Platelet VASP phosphorylation was significantly reduced in diabetic WT but not in diabetic GCH-Tg mice. P-selectin, CD40 ligand expression, and fibrinogen binding were increased in diabetic WT mice but remained unchanged compared with controls in endothelial-targeted GCH-Tg mice. CONCLUSIONS: Platelet activation results from acute and chronic reduction in NO bioactivity. Rescue of platelet activation in diabetes by endothelial-specific restoration of NO production demonstrates that platelet function in vivo is principally regulated by endothelium-derived NO. Endothelial dysfunction caused by uncoupling of endothelial NO synthase is well described in diabetes mellitus and may lead to platelet activation. Acute loss of systemic NO bioavailability causes platelet activation. eNOS uncoupling prevention in diabetes preserved systemic NO bioavailability and maintained a physiological platelet state without activation in vivo.